Bibliographies
This file holds a collection of bibliographies that is to say a coll ection of different authors together with their corresponding titles. S ome of these bibliographies include bibliography on higher education, M akerere University-various documents/publications, complete bibliograph y of Makerere University publication, 1900-1996, bibliography of Uganda n bibliographies: the legacy of Prof. Bryan Langlands
AR/SIC/3/7
English
Shelf no. 3
Keywords: Bibliography